A predominant Th1 polarization is present in synovial fluid of end-stage osteoarthritic knee joints: analysis of peripheral blood, synovial fluid and synovial membrane. (22nd November 2018) - Rosshirt, N; Hagmann, S; Tripel, E; Gotterbarm, T; Kirsch, J; Zeifang, F; Lorenz, H-M; Tretter, T; Moradi, B
Summary: Thorough understanding of the complex pathophysiology of osteoarthritis (OA) is necessary in order to open new avenues for treatment. The aim of this study was to characterize the CD4 + T cell population and evaluate their activation and polarization status in OA joints. Fifty-five patients with end-stage knee OA (Kellgren–Lawrence grades III–IV) who underwent surgery for total knee arthroplasty (TKA) were enrolled into this study. Matched samples of synovial membrane (SM), synovial fluid (SF) and peripheral blood (PB) were analysed for CD3 + CD4 + CD8 – T cell subsets [T helper type 1 (Th1), Th2, Th17, regulatory T cells] and activation status (CD25, CD69, CD45RO, CD45RA, CD62L) by flow cytometry. Subset-specific cytokines were analysed by cytometric bead array (CBA). SM and SF samples showed a distinct infiltration pattern of CD4 + T cells. In comparison to PB, a higher amount of joint-derived T cells was polarized into CD3 + CD4 + CD8 – T cell subsets, with the most significant increase for proinflammatory Th1 cells in SF. CBA analysis revealed significantly increased immunomodulating cytokines [interferon (IFN)-γ, interleukin (IL)-2 and IL-10] in SF compared to PB. Whereas in PB only a small proportion of CD4 + T cells were activated, the majority of joint-derived CD4 + T cells can be characterized as activated effector memory cells (CD69 + CD45RO + CD62L – ). End-stage OA knees are characterized by an increased CD4 + T cell polarization towards activated Th1 cells and cytokine secretion compared to PB. This local inflammation may contribute to disease aggravation and eventually perpetuate the disease process. Graphical Abstract: